Assessment Of Quality Of Life Amongst Oral Cancer Patients: A Prospective Questionnaire Based Study - Sahin, Ibtisam; Mehra, Hemant; Tandon , Sapna; Chauhan, Himanshu; Singh, Gaurav; Kumar, Aakash (Journal of Neonatal Surgery, 2025)
Introduction: Oral cancers are one of the most prevalent cancers worldwide, with significant health implications. The management of oral cancer often involves a combination of surgery, radiotherapy, and chemoradiotherapy, which while life-saving can lead to profound consequences on patient’s physical, psychological & social wellbeing. Aim: To Evaluate QOL in oral cancer patients & assess the variables predicting the difficulty in mastication, swallowing and salivation after treatment, like surgical resection and chemoradiotherapy. Method: A total of 82 patients were recorded qualifying the inclusion criteria of Biopsy proven Oral squamous cell carcinoma, Clinical TNM stage III & IV, No evidence of distant metastasis, No history of recurrence of cancer, and who would be Reconstructed at the time of surgical resection with distant flap. set of questionnaire comprises of data regarding quality of life Results: The progression of patients' quality of life (QOL) was evaluated across three visits during the treatment period, revealing significant improvements over time. At the initial assessment, none of the patients reported a "Good" QOL. The majority were categorized as having a "Satisfactory" QOL. Notably, the "Satisfactory" and "Poor" QOL categories were entirely eliminated, indicating a universal enhancement in patients' well-being. Conclusion: Quality of life is a concept that has become increasingly important in relation to patient outcomes following treatment for cancer.. The present analysis of patient-reported QOL outcomes may help guide treatment decisions for patients with OSCC based on accurate expectations of adverse effects of cancer treatment..